A Positive Impacts: Empowering Women in Small and Medium-Sized Enterprises (SMEs) of Packaged Dry Food as a Poverty Alleviation Effort in Rural Areas of Semarang Regency - Sutrisno; Prabowo, Heri; Faizza, Tria; Heriyanto, Rizal; Jauhari, Mohamat (PT. LITERASI SAINS NUSANTARA, 2024)
Semarang Regency is an area comprising several rural regions with relatively high poverty rates. Women often play an integral role in micro, small, and medium-sized enterprises (MSMEs) in rural areas. This research aims to analyze the empowerment strategies of women in MSMEs of packaged dry food as a poverty alleviation effort in rural areas of Semarang Regency. The research method employed is a literature review with a qualitative approach and descriptive analysis focusing on community service contributions. Data will be gathered from scholarly articles published between 2011 and 2024 through the academic source Google Scholar. The study findings indicate that within the context of Semarang Regency, women in rural areas have found new strengths in facing global economic challenges. Through empowerment in MSMEs of packaged dry food, they not only create marketable products but also pave the way towards economic self-sufficiency and equitable social change. Support from various stakeholders, such as the government, non-governmental organizations, and the private sector, has been a strong pillar in their journey. Despite challenges like limited access to resources and inadequate infrastructure, the resilient spirit of these women continues to drive them forward.